SERAPAN FOSFOR PADA PADI SAWAH SRI (System of Rice Intensification) DAN SISTEM KONVENSIONAL PADA JARAK TANAM YANG BERBEDA - , RINANDA INNEKE PUTRI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Differences in the plant spacing of this study aims to determine the phosphorus nutrient uptake, plant growth and crop production on two different methods of cultivation, they are SRI and Conventional. The research was conducted in December 2012 until March 2013 in the form of field research on longland area of Ngestiharjo village, Wates district, Kulonprogo Regency, Daerah Istimewa Yogyakarta. Treatments consisted of two methods of rice cultivation with different plant spacing treatments, transplanting age and fertilization. Results of this study showed that the highest availability of P is in the treatment of SRI. The growth of paddy rice with SRI cultivation method (panicle length, filled grains weight, wet and dry weight of plants, wet and dry weight of root crops ) is higher than conventional rice cultivation method. Based on the research data, the highest P uptake is 2.64 mg/clump on J2U2P2 treatment. Harvested dry grain by equal number of plants per plot at SRI method is higher than conventional farming in the amount of 22.45 kg/Plot on J2U2P2 treatment.